The significance of maximal squat strength for neuromuscular knee control in elite handball players: A cross-sectional study - Augustsson, S. R.; Gannby, E. (Sports, 2023)
Both weak muscle strength and impaired neuromuscular control has previous been suggested as risk factors for future traumatic knee injury. However, data on the relationship between these two factors are scarce. Thus, the aim of this study was to investigate the relationship and influence of the one repetition maximum (1RM) barbell squat strength on dynamic knee valgus in elite female and male handball players. In this cross-sectional study 22 elite handball players (7 females) were included. A unilateral drop jump (VDJ) test was used for the assessment of frontal plane dynamic knee valgus. Players also performed a one repetition maximum (1RM) barbell squat test, expressed relative to bodyweight (r1RM), to assess maximal strength, which were dichotomized to analyze `weak` versus `strong` players according to median. Correlations were noted between r1RM in squat and knee valgus angle for both the non-dominant (r = -0.54; p = 0.009) and dominant leg (r = -0.46, p = 0.03). The odds of knee valgus were eight times higher, for the dominant leg, in the weak group compared to the strong group (p = 0.03) and 27 times higher, for the non-dominant leg (p = 0.002). The outcome of the present study suggests that maximum squat strength plays an important role when it comes to neuromuscular control of the knee, and that weak handball players are at higher risk of knee valgus compared to strong players during jumping activity.